Alberto Masferrer, Augusto César Sandino: Antiimperialismo, espiritualismo y utopía en la década de 1920 - López Bernal, Carlos Gregorio (Revista Complutense de Historia de América, 2010)
This work studies some aspects of the thought of Alberto Masferrer (1868-1932) and Augusto César Sandino (1895-1934), in the context of the new intellectual tendencies that appear in Latin America at the beginning of the 20th century. Althought they were incompatible in some aspects, this study intends to show that they also coincided; furthermore, they had many subjects in common with other writers at that time. The aim is to present similarities in the ideas of Masferrer and Sandino, analyzing the historical context in which they lived and worked, and their relationships with other intellectuals of the region. Their spiritualism and theosophical thinking is studied, as well as the way that these ideas conditioned their reformist political proposals and, in some ways, may have helped them to accept the failure of their social and political projects.